Left atrial deformation parameters among beta-thalassemia major patients. (14th October 2021) - Patsourakos, D; Aggeli, C; Gatzoulis, K; Delicou, S; Dimitroglou, Y; Androulakis, A; Tsioufis, K
Abstract: Introduction: Atrial cardiomyopathy is present in a significant proportion of beta thalassemia major (β-TM) patients, complicating their clinical condition. The diagnosis of atrial cardiomyopathy is challenging using conventional echocardiographic techniques. Purpose: In our study we aimed to identify the presence of atrial cardiomyopathy by applying novel echocardiographic techniques in these patients. Methods: 56 β-TM patients (mean age 39.3±9 years, 50% male sex) and 30, age and sex matched, healthy controls were examined by transthoracic echocardiography. Conventional echocardiographic parameters were estimated alongside with deformation indices (left atrial strain at reservoir (LASr), conduit (LAScd) and contraction (LASct) phase respectively as well as left ventricular global longitudinal strain (GLS)). T2* was calculated by cardiac magnetic resonance imaging in β-TM patients. Results: LAVI, E/e' ratio, GLS and left atrial deformation parameters differed between patients and controls. In patient group, left atrial deformation indices were correlated with LAVI, E/e' ratio, GLS and T2* (Table 1). GLS was also correlated with LAVI, but not with T2* or E/e' ratio. T2* was correlated only with left atrial deformation indices. Patient with prior episodes of atrial fibrillation were older, had increased E/e' and LAVI and impaired left atrial deformation indices but did not differ in terms of GLS or T2* (Figure 1). Patients with iron overload differed only in terms of left atrial deformation parameters. Conclusions: Atrial deformation indices could be of clinical use in the early detection of atrial cardiomyopathy. Impaired left atrial strain may be associated with silent atrial fibrillation and be indicative of myocardial iron overload. Funding Acknowledgement: Type of funding sources: None.